Mixed convection boundary layer flow embedded in porous medium with nanofluids - Mat Yasin, Mohd Hafizi (2013)
Convective flow and heat transfer in a saturated porous medium has been the subject of many investigations during the last decades and has been extensively studied. This fact has been motivated due to the importance of this process which occurs in many engineering and natural systems. An analysis of the steady mixed convection boundary layer flow past a vertical surface embedded in a porous medium saturated by a nanofluid is performed in this thesis. The objective of this thesis is to investigate the effect of internal heat generation, effect by using stratified porous medium and effect of suction and injection for present problem. The effect of internal heat generation is important in several applications including reactor safety analysis, metal waste form development for spent nuclear fuel, fire and combustion studies, and storage of radioactive materials.The similarity equations are solved numerically for three types of metallic or nonmetallic nanoparticles such as copper (Cu), alumina (A1₂O₃) and titania (TiO₂), in a water-based fluid to investigate the effect of the solid volume fraction or nanoparticles volume fraction parameter ⱷ of the nanofluid on the flow and heat transfer characteristics with suction or injection. Shooting method from MAPLE is used to solve the problem. This well-known technique is an iterative algorithm which attempts to identify appropriate initial conditions for a related initial value problem (IVP) that provides the solution to the original boundary value problem (BVP). The surface velocity, the local Nusselt number, the velocity profiles and temperature profiles are presented and discussed. Based on the results, it is noticed that these parameters can be used to control the convection boundary layer flow. The suction or injection parameters have the effects to increase the thermal boundary layer thickness, thus reduce the heat transfer at the interface.